2016
DOI: 10.25011/cim.v39i6.27505
|View full text |Cite
|
Sign up to set email alerts
|

Does Tinnitus Lead to Depression?

Abstract: Purpose: The aim of the study was to investigate the correlation between THI (Tinnitus Handicap Inventory) and BDS (Beck Depression Scale). Materials and Methods:High frequency thresholds and PTA (Pure Tone Audiometer) thresholds for the patients were measured in 44 patients with tinnitus (bilateral=13; unilateral=31). Tinnitus frequency and intensity were measured using one-pair method with high frequency audiometer Interacoustic AC40. Applied BDS and THI scores are evaluated for all patients. Our findings ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
(14 reference statements)
0
7
1
1
Order By: Relevance
“…The depressive symptoms were also assessed by using different multi-item questionnaires. The BDI was used in 15 studies ( 42 , 52 54 , 60 63 , 65 , 66 , 68 , 69 , 74 ), HADS-D was used by seven studies ( 43 – 46 , 59 , 71 , 72 ), CES-D by four studies ( 16 , 51 , 55 , 73 ), SDS by three studies ( 47 , 50 , 58 ), SCL-90R ( 48 , 56 ). The MMPI and the PHQ-9 were both used once in two different studies ( 49 , 57 ) ( Tables 4–6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The depressive symptoms were also assessed by using different multi-item questionnaires. The BDI was used in 15 studies ( 42 , 52 54 , 60 63 , 65 , 66 , 68 , 69 , 74 ), HADS-D was used by seven studies ( 43 – 46 , 59 , 71 , 72 ), CES-D by four studies ( 16 , 51 , 55 , 73 ), SDS by three studies ( 47 , 50 , 58 ), SCL-90R ( 48 , 56 ). The MMPI and the PHQ-9 were both used once in two different studies ( 49 , 57 ) ( Tables 4–6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Depression was related to tinnitus with normal hearing in the current study. Several previous studies have reported elevated rates of depression in patients with tinnitus [ 17 , 18 ]. A cross-sectional study using a national health survey demonstrated 4.8-fold higher odds of depression in patients with tinnitus (95% CI = 3.5–6.7, p < 0.001) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the study did not consider the level of hearing of the participants; thus, the influence of hearing loss in tinnitus could not be distinguished from the relationship between tinnitus and depression. Another study demonstrated a positive correlation between tinnitus and symptoms of depression [ 18 ]. Specifically, the frequency of tinnitus correlated with depression ( r = 0.6, p = 0.001), and the intensity correlated with the Beck Depression Scale ( r = 0.28, p = 0.13) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with tinnitus were determined to have higher mean scores for depressive symptoms than healthy individuals. A large-scale study conducted in America included approximately 21.4 million, wherein those with tinnitus (anxiety in 26.1% and depressive symptoms in 25.6%) were higher than those without (anxiety in 9.2% and depressive symptoms in 9.1%) 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%